Hopx(+) optic nerve head-astrocytes counter neuronal stress and glaucoma damage - Steven L. Bernstein; Zara Mehrabian; Yan Guo; Jean Jouffroy; Ben Mead; Stanislav Tomarev; Esmahan Durmaz; Jonathan A. Epstein; Adam Kronk; Seth Blackshaw; Thanh Hoang (Proceedings of the National Academy of Sciences, 2026)
Retinal ganglion cell (RGC) axons form the optic nerve (ON). Numerous age-related ON diseases, including glaucoma, the second most common cause of worldwide blindness, result from multiple RGC stressors. Nearly all ON astrocytes in the optic nerve head (ONH): the junctional region between the ON and the retina in young-adult rodents expresses the homeodomain only (Hopx) protein. Hopx(+) ONH astrocytes are depleted during aging. ONH primary cultures which include Hopx(+) astrocytes secrete extracellular vesicles (ONH-EVs) which selectively enhance RGC survival and neurite extension in culture, while extracellular vesicles (EVs) secreted from distal ON cultures lacking Hopx(+) astrocytes do not. ONH-EVs also enhance RGC survival in vivo in a rodent model of glaucoma. Combining rat ONH single-cell (scRNA-seq) sequencing with EV proteomic analysis, we identified ONH-Hopx(+) astrocyte secreted factors. We interrogated the online Broad institute scRNA-seq database for rat RGC gene expression in control animals and following rodent ON crush, an RGC stress model, to correlate ONH-astrocyte secreted factors with RGC gene expression changes. Following stress, RGCs upregulate the complementary pathways involving Hopx(+) astrocytic-associated factors, suggesting reciprocal communication. Using a highly selective transgenic Hopx-cre ONH knockdown strategy, we demonstrate that eliminating Hopx(+) astrocytes also results in upregulation of RGC stress responses. Our results implicate age-related loss of young ONH-astrocytes as a crucial factor in the development of age-related optic nerve diseases, and discuss replacing ONH associated factors as a paradigm shift for ON disease treatment.